AVALIAÇÃO DA CONFIGURAÇÃO DA ESTRUTURA CICLOVIÁRIA DE CAMPO GRANDE (MS) - Kamila de Aguiar Duarte (2023)
The growing population growth in urban centers brings up some challenges for public managers and society, such as urban mobility. Official data show that Campo Grande, capital of Mato Grosso do Sul, has been facing traffic problems arising from the surplus of vehicles, potentially polluting, traveling in the city. In this sense, the occasion of traffic jams, air pollution and urban stress have placed the bicycle as a modal alternative capable of reducing the damage caused by the excessive use of motor vehicles in cities. Bicycles, when aligned with the sustainable and intelligent integration of cycling infrastructure, can act as a facilitating mechanism for commuting, being a healthy and more accessible mode of transport, in addition to contributing to the mitigation of climate emergencies. From such perspectives, it is questioned whether the current configuration of the bicycle structure built in Campo Grande (MS) acts as a sustainable and intelligent mobility solution. Thus, the general objective of this study is to evaluate the configuration of the bicycle structure in the city of Campo Grande (MS). Specifically: a) Carry out a survey of the literature on Sustainable and Smart Cities, as well as legislative and normative contributions regarding the use of the bicycle modal in Brazil; b) Evaluate the cycling infrastructure, already implemented in the urban perimeter of Campo Grande (MS); c) Analyze potential points and weaknesses of the bicycle structure in Campo Grande (MS); d) Prepare a Technical-Technological Report with proposals to promote smart and sustainable mobility in Campo Grande (MS). For that, a qualitative study was developed, through an exploratory, descriptive and applied research, associated with the necessary bibliographic survey and application of a field study. Then, the comparative method was applied, based on the IDECiclo and QualIClo scales, to enable the qualification of the Copenhagenize Index parameters, which evaluate the quality and size of the infrastructure, with the purpose of promoting the use of bicycles in cities. Based on the triangulation analysis of the methods applied in the research, the results showed a cycling structure classified as sufficient, but with reservations in terms of comprehensive care for intelligent and sustainable mobility, and, consequently, the achievement of the goals contained in the Sustainable Development Goals.